Application of a multiplex CRISPR/Cas9 strategy for elimination of selection markers from transgenic plants - Rafi, Mohammed; ElSiddig, Mohamed; Aldarmaki, Maitha; Al Nuaimi, Mariam; George, Suja; Amiri, Khaled M. A. (Frontiers in Genome Editing, 2025)
Selectable marker genes (SMGs) are essential for identifying transgenic plants but raise concerns regarding biosafety, regulatory compliance, and public acceptance. In this study, we used a CRISPR/Cas9-based strategy to eliminate the SMG from transgenic tobacco plants. Leaf discs from plants carrying DsRED (SMG) and aminoglycoside phosphotransferase (gene of interest, GOI) were re-transformed with a CRISPR vector containing four gRNAs designed to target both flanking regions of the SMG cassette. Approximately 20% of the regenerated shoots exhibited loss of red fluorescence, and PCR and sequencing analyses confirmed that about half of these carried a smaller amplicon, indicating a successful SMG excision efficiency of around 10%. Mutation analysis further revealed the presence of small indels at gRNA target sites, in addition to the deletion of SMG cassette. Quantitative real-time PCR (qPCR) analysis confirmed the absence of DsRED expression in SMG-deleted lines, while the Cas9 and GOI remained actively expressed. The SMG-free plants displayed normal growth, flowering, and seed production, indicating CRISPR marker excision had no adverse effects on plant development and fertility. In addition, Cas9-free, marker-free transgenic plants were recovered through segregation in T1 generation. This approach is adaptable to various transgenic plant species and provides a practical solution for generating marker-free transgenic crops, thereby enhancing their acceptance and commercialization.